Critiquing the Concept and Practices of Domestic Tourism in Nepal (Nepalese Journal of Hospitality and Tourism Management, 2022)
Nepal is a very rich country in terms of its natura beauty along with cultural variety. It has been an attraction for not only the foreigners but also domestic travellers. However, the contribution of domestic tourism in the development of this sector has been overlooked. After the Covid-19 pandemic, domestic tourism is in the stage of commercialisation. In this context, this paper aims to critique the concept and practices of domestic tourism in Nepal in view of the analysis of the existing problems and prospects in fostering domestic tourism in Nepal. This study is based on reviewing the various related literatures. The study finds lack of strategic plan, lack of meaningful collaboration and consensus in policy development among the various tiers and actors of the government, less travel culture of the people, inadequate infrastructures, insufficient organisation, lack of forward and backward linkages and human resource capability as major problems whereas natural and cultural diversities, increasing focus of different tiers of government, popularisation of new destinations through social media, growing interest in domestic tourism, indefinite pandemic, growing travel culture in urban areas, popularity of home stays, growing number of skilled manpower in the sector are the prospects of domestic tourism in our country.